EUS-Guided gallbladder drainage vs percutaneous transhepatic drainage in patients with acute cholecystitis: a systematic review and meta-analysis - Guzmán-Calderón, Edson (2023)
Occasionally, cholecystectomy is not possible because the patient is not suitable for surgery, and non-operative management should be performed. In these patients, the non-operative management can be through the percutaneous transhepatic gallbladder drainage (PTGBD) or the endoscopic gallbladder drainage. We decided to compare the efficacy and safety of PTGBD and EUS-GBD in the non-operative management of patients with acute cholecystitis. We conducted a systematic review in different databases, such as PubMed, OVID, Medline, and Cochrane Databases. This meta-analysis considers studies published until September 2021. Six studies were selected (2 RCTs). These studies included 749 patients. The mean age was 72.81 ±7.41 years, and males represented 57.4%. EUS-GBD technical success was lower than PTGBD (RR, 0.97; 95% CI, 0.95-0.99), whereas clinical success and adverse events rates were similar in both groups. Twenty-one deaths were reported in all six studies. The global mortality rate was 2.80%, without differences in both groups (2.84% and 2.77% in the EUS-GBD group and the PTGBD groups, respectively). EUS-GBD and PTGBD were successful techniques for gallbladder drainage in patients with acute cholecystitis who are non-tributary for surgery. EUS-GBD has a similar clinical success rate and a similar adverse events rate in comparison to PTGBD. The high technical success and the low adverse events rate of the EUS approach to gallbladder make this technique an excellent alternative for patients with acute cholecystitis who cannot be undergoing surgery.